Giant optical anisotropy of WS2 flakes in the visible region characterized by Au substrate assisted near-field optical microscopy. (20th August 2022) - Deng, Nan; Long, Hua; Wang, Kun; Han, Xiaobo; Wang, Bing; Wang, Kai; Lu, Peixiang
Abstract: Transition metal dichalcogenides (TMD) have attracted considerable attention in the field of photonic integrated circuits due to their giant optical anisotropy. However, on account of their inherent loss in the visible region and the difficulty of measuring high refractive index materials, near-field characterizations of the optical anisotropy of TMD in the visible region have inherent experimental difficulties. In this work, we present a systematical characterization of the optical anisotropy in tungsten disulfide (WS2 ) flakes by using scattering-type scanning near-field optical microscopy ( s -SNOM) excited at 671 nm. Transverse-electric and transverse-magnetic (TM) waveguide modes can be excited in WS2 flakes with suitable thickness, respectively. With the assistance of the Au substrate, the contrast of the near-field fringes is enhanced in comparison with the SiO2 substrate. By combining waveguide mode near-field imaging and theoretical calculations, the in-plane and out-of-plane refractive indexes of WS2 are determined to be 4.96 and 3.01, respectively, indicating a high birefringence value up to 1.95. This work offers experimental evidence for the potential application of WS2 in optoelectronic integrated circuits in the visible region.